A Systems Thinking Approach to the Development of HBIM: Part 1—The Problematic Situation - Lucy J. Lovell; Richard J. Davies; Dexter V. L. Hunt (Heritage)
Building Information Modelling (BIM) is an information management and modelling technique frequently employed by the Architecture, Engineering, and Construction (AEC) sector. The application of BIM to Cultural Heritage (CH), otherwise known as Historic BIM (HBIM), will assist with the ongoing sustainable management of CH. However, the application of HBIM is currently limited by a lack of defined end-user requirements and standard methodology in its application. To address this, the authors propose a systems thinking approach, utilising both the Soft Systems Methodology (SSM) and hard Systems Engineering (SE), for the development of HBIM. Subsequently, this paper presents the results of an extensive survey undertaken with the United Kingdom (UK) Heritage Community to identify challenges faced by the CH sector and utilises the SSM to propose the core purpose of HBIM within the CH sector. The responses to the survey suggest that the development of HBIM should prioritise the promotion of structured information management instead of the generation of detailed geometric models, a key theme of much existing research. Future work by the authors (Part 2 of this work) will continue the analysis of the survey results and utilise SE processes to define end-user requirements for HBIM.